Ранньопалеолітичне місцезнаходження Суходол у Середньому Подонцов'ї - Скоріков, В.А. (Археологія, 2015)
В восточном регионе Украины, в среднем течении р. Северский Донец, на сегодня выявлены три памятника с галечным инвентарем: Вишневый Дол, Штурманское и Суходол. Настоящая статья вводит в научный оборот ма- териалы местонахождения Суходол. В коллекции местонахождения широко представлены изделия на гальках. Технико-типологические признаки позволяют однозначно сопоставлять инвентарь с развитыми олдувайскими индустриями. Галечные чопперы, чоппинги и другие архаичные формы сопровождаются изделиями на кварците, также имеющими архаичные технико-типологические черты. Вопрос о точном возрасте выявленных коллекций остается открытым, поскольку материалы выявлены в поверхностном залегании. Указанием на хронологию на- ходок могут служить технико-типологические параллели с материалами эоплейстоцен-раннеплейстоценового возраста, выявленными в Приднестровье, на Тамани и в Дагестане. Ближайшие типологические аналоги можно отчасти видеть в галечных формах Байраков в Приднестровье, Меджибожа в Побужье и, в особенности, Гаспры в Крыму. В предварительном плане можно допускать, что уже в эоплейстоцене—раннем плейстоцене территория Среднего Подонцовья была достаточно уверенно освоена древними гоминидами. Three sites with pebble inventory are discovered by this day in the eastern region of ukraine in the Siverskyi Donets River middle flow area, namely, vyshnevyi Dol, Shturmanske, and Sukhodil. Materials of Sukhodol are introduced into the scientific turn in this article. the products made of pebbles are widely represented in the collection from the locality. technological and typological features allow the author to undoubtedly correspond the inventory with the developed oldowan industries. Pebble choppers and choppings and other archaic firms are accompanied with the products made of quartz also having the archaic technological and typological features. the issue of precise age of the collections discovered remains to be unsolved, because the materials are found in the surface deposit. technological and typological parallels with the materials of the Eopleistocene (Early Pleistocene) age found in the Dnister River region, in taman, and Dagestan, can serve as a chronological indication for the finds. the nearest typological analogies can be partly seen in the pebble forms from Bairaky in transnistria, Medzhybizh in the Buh River region, and especially from haspra in the Crimea. It can be preliminarily presumed that the territory of the Donets River middle flow area was quite certainly settled by the ancient hominins already in Eopleistocene (Early Pleistocene).